Disfungsi Komunikasi Pemerintah Desa Dalam Tata Kelola Penyaluran Bantuan Sosial Di Desa Yosowilangun Kabupaten Lumajang - Teza Putri Indahsari; Baktiawan Nusanto (Lembaga Teewan Journal Solutions, 2026)
This study critically examines how communication dysfunction within the village government structure affects the quality of social assistance distribution governance in Yosowilangun Village, Lumajang Regency. The issue is particularly pertinent given the persistently high rate of inaccurate targeting in village-level social assistance distribution, a problem whose roots are rarely traced systematically to the dimension of institutional communication. Employing a descriptive qualitative approach with a systematic literature review method, this article synthesizes findings from recent scholarly works and contextualizes them within the local realities of Yosowilangun Village. The findings reveal that communication dysfunction manifests in several concrete forms, including information distortion among actors within the village governance hierarchy, limited transparency in the beneficiary verification process, weak community feedback channels, and message inconsistency between village apparatus and recipient communities. These conditions structurally undermine good governance principles that ideally should underpin equitable and well-targeted social assistance distribution. This research makes a theoretical contribution by integrating an institutional communication perspective into the analysis of village governance, an approach that remains underexplored in Indonesian political science and public administration literature. The findings also formulate several communication-based policy recommendations that can be practically implemented at the village level.